ECONOMIC ANALYSIS DEVELOPMENT “X” FIELD USING PSC GROSS SPLIT SYSTEM IN Y COMPANIES - Agung Indra Wijaya (Jurnal Eksakta Kebumian, 2020)
PSC Gross is a PSC without cost recovery where the division between the government and oil and gas companies directly from gross revenues. The emergence of this contract system led to the recovery of costs in the previous contracting system which deemed less effective. By implementing this contract system, it is expected that contractors can use investment and operational costs more efficiently. With the PSC Gross Split, it is also expected to increase the spirit of field development. In the JM Block, the economic calculation using PSC Gross Split results in a better economy than PSC Cost Recovery. To appreciate the feasibility of this development by looking at economic indicators that support to obtain high oil selling prices. These indicators are an attempt to make a decision regarding the development of the "X" Field which is  an economical and profitable business. Keywords Gross Split PSC, PSC Cost Recovery, Development, Economical, Profitable